Preoperative Education Against Anxiety on Patient Pre Retinal Ablasio Surgery at The Eye Hospital Invitation Surabaya - Dewi Retno Puspitosari; Suhartini; Nurhidayah (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Retinal detachment is a disease of decreased vision due to the separation of the retinal cone cells and rod cells from the retinal epithelial cells.  The most common response in preoperative patients is anxiety.  Preoperative anxiety can cause palpitations, palpitations, feeling like fainting, increased blood pressure, and increased pulse pressure.  The purpose of this study was to determine the effectiveness of providing preoperative education on anxiety in preoperative retinal detachment patients at Undaan Eye Hospital, Surabaya.  The research design was a quasi-experimental study with a one group pre-test – post-test design approach.  The results showed that the patient's anxiety level before being educated was half of the respondents with severe anxiety, the anxiety level after being educated was almost half of the respondents who had no anxiety and mild anxiety.  Based on SPSS calculations using the dependent sample t-test, the value of p = 0.000 (<0.05) is obtained at the sig.(2.tailed) value.  So, there is a difference in the level of anxiety before and after being given education to preoperative retinal detachment patients at the Undaan Eye Hospital, Surabaya.  This means that the education given to preoperative retinal detachment patients is effective in reducing anxiety levels.  The conclusion of this research is that there is effectiveness in providing education on anxiety levels at the Mata Undaan Hospital, Surabaya.